Updating the European Union's regulation on classification, labelling and packaging of substances and mixtures (CLP): A key opportunity for consumers, workers and stakeholders with interests in the legislation and toxicology of hazardous chemicals. (2021) - Vinceti, Silvio Roberto; Docea, Anca Oana; Tsitsimpikou, Christina; Filippini, Tommaso
Graphical abstract: Highlights: Public consultation to update CLP regulation has launched. Envisaged revisions will go beyond the classification and labelling of chemicals. Endocrine disruptors and two categories of persistent toxic chemicals are proposed. Main domains are environmental contamination, chemical mixtures and laboratory animals use. Abstract: Recent advancements in toxicology and the European Union's Green Deal, with its Chemicals Strategy for Sustainability, have paved the way for major changes in EU legislation on the control of environmental chemicals for a cleaner and safer environment. Another substantial legislative advancement underway is the update of the "Regulation on Classification, Labelling and Packaging of Substances and Mixtures (CLP), " an ambitious piece of EU legislation with exceptional scientific toxicological background in identifying a hazard, aiming at better protecting its citizens and the environment from the risk of chemical substances and products, the occupational settings included. Update of CLP legislation additionally aims at facilitating the free exchange of chemicals in the European Internal Market, provided that proper labelling and packaging processes are implemented. Participation in the ongoing online public consultation on these issues, ending on November 15, 2021, is of key relevance to ensure a transparent and effective definition of such an important piece of legislation, fully compliant with current EU priorities in terms of human and environmental protection and animal welfare.